'The rock that can't be moved': China's revised geostrategies in Myanmar. Issue 1 (2nd January 2019) - Lanteigne, Marc
ABSTRACT: Since 2011, Myanmar has undertaken a series of domestic and foreign policy reforms, including democratisation and peacebuilding, before and after the watershed November 2015 elections in the country. These reform processes have called into question whether China, which has been Myanmar's dominant great power neighbour throughout the previous era of military government in the country formerly known as Burma, would find its strategic position eroding as Myanmar further opens to the international community. However, the concept of China 'losing' diplomatic ground to other actors, including the West, in Myanmar implies a zero-sum game that does not adequately address Beijing's still-formidable geostrategic presence vis-à-vis its southern neighbour. China has now started to implement a more multi-faceted, 'resilience network'-building approach to maintaining its special status in Myanmar's foreign policy, a situation which will persist as Myanmar continues its uncertain path towards further reform.